Glandula Tiroid Problem: Literature Review - Abdul Hafiz, Muhammad Zaki; Daan khambri (Biomedical Journal of Indonesia, 2021)
Thyroid cancer is the most common endocrine system neoplasm.Based on the "Pathologycal Based Registration" in Indonesia, thyroidcancer is a cancer with the highest incidence in the ninth rank.According to statistics from the National Cancer Institute (NCI), theincidence of thyroid cancer in men is about 2.5 per 100.000population and women around 6.7 per 100.000 population. Thyroidcancer can affect all age groups and the frequency increases afterthe age of 50 years. Only about 5% can affect the age of 15-20 years.NCI also states that this thyroid cancer can affect 16.000 people peryear. Diagnosis is important to improve the quality of life forsufferers. Clinical diagnosis is the basis for determining furthermanagement, so that knowledge and skills are needed indetermining the diagnosis. The first treatment for a cancer is thebest chance for the patient to achieve optimal cure rates, as is thecase for thyroid cancer.